Peningkatan Hasil Belajar Siswa Melalui Media Power Point di Kelas II SD Negeri 105290 Desa Kolam - Leni Malinda (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine the use of power point media in improving student learning outcomes on the theme of togetherness in class II SD Negeri 105290 Desa Kolam. This type of research is classroom action research (classroom action research). The subjects of this study were the second grade students of SD Negeri 105290 in Desa Kolam with a total of 35 students. The indicators that can be formulated by the author are: an increase in Togetherness thematic learning outcomes, which have reached the KKM (Minimum Completeness Criteria). The use of example non-example learning models assisted by power point media in the material of togetherness in class II SD Negeri 105290 Desa Kolam is able to improve student learning outcomes. This is evidenced from the pre-action test with 53.33% l learning completeness to the first cycle with 76.67% classical learning completeness and an increase in the second cycle by 86.67%. Keywords: Learning Outcomes, Power Point Media